Corruption and Its Eradicate Strategies - Hendrarto Hendrarto; Endang Larasati; Triyuniningsih Triyuniningsih; Sri Suwitri (Budapest International Research and Critics University, 2021)
The Effort to eradicate corruption in Indonesia have actually been done for a long time, namely during the age of corruption itself. Since Indonesia was independent from Dutch colonialism, corruption eradication in Indonesia can be divided within 3 periods, namely during the old order, the new order and the reform order. However, until now it has not been said to be successful, this can be seen from the order of Indonesia that remains low in the eradication of corruption around the world. The strategies used in this case include institutional hesitant strategies. Because less effective than the necessity to be another, tougher strategy to overcome it. One strategy that fits with Indonesia's current situation and condition is to use a hard and radical strategy, namely determined institutional strategy. By using that strategy, it is intended being able to take systematic and coordinated actions, in order to detect and punish corruptors, while also looking for the cause of corruption. This way Indonesia will be able to solve the problem of corruption faced.